Pengaruh Foreign Direct Invetment, Ekspor dan Konsumsi Energi Terhadap Pertumbuhan Ekonomi Indonesia - Sari, Firanda Puspita; Muslinawati, Retno; Adianita, Happy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study was conducted to examine and provide empirical evidence regarding the influence of Foreign Direct Investment (FDI), exports, energy consumption on GDP in 2009-2023. This study uses secondary data from the World Bank, an associative quantitative approach. The data were analyzed using multiple linear regression of time series data through the Eviews program version 12. The variables are Foreign Direct Investment (FDI) X1 exports X2 energy consumption X3 and economic growth (Y). The results of the study show that Foreign Direct Investment (FDI) has no influence on economic growth with a probability value of 0,8561 (<0,05), a coefficient of -0,022959, while exports have a positive influence on economic growth with a probability value of 0,0014 (<0,05), a coefficient of 0,144058, and energy consumption has a negative effect on economic growth with a probability of 0,0088 (<0,05), a coefficient of -0,161483. The coefficient of determination is 57,92% and the rest is influenced by variables outside the study.